SUSTAINABILITY AND ENVIRONMENTAL CHALLENGES OF MODERN SHIPPING INDUSTRY - Hasanspahić, Nermin; Vujičić, Srđan; Čampara, Leo; Piekarska, Klaudia (Journal of Applied Engineering Science, 2020)
Nowadays, maritime transport faces more challenges than at its beginning. Like any other industry, the maritime sector must adapt to the needs of the modern world and carry out its activities with respect for the environment. Continuous technological development and increased environmental awareness are the determining factors of changes in modern shipping. Therefore, one of the main challenges of maritime transport is to implement innovative solutions to protect the marine environment. However, it is quite challenging to achieve both ecological and economic benefits at the same time. That is why it is very important to apply the win-win principle, which refers to the sustainable development of maritime transport. The paper provides an overview of applicable and promising technological solutions, logistical activities, and regulatory provisions applied in reduction of shipping gas emissions, as well as importance of points to be considered in development of sustainable shipping. Innovative methods of adapting to the increasingly restrictive environmental regulations are presented as well.
Keywords: maritime transport; ship; environment; noxious emissions; green logistics; sustainability